PEMBERDAYAAN MASYARAKAT MELALUI PENYULUHAN TANAMAN HIDROPONIK MEMBENTUK WIRAUSAHA BARU DI DESA BUMISARI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Gatot Bintoro Putra Aji (Yayasan Baitul Hikmah al-Zain, 2026)
Hydroponic vegetable cultivation for the community of Bumisari Village aims to produce safe and economically valuable household-scale vegetables. This community service activity was conducted in Bumisari Village, Natar District, South Lampung Regency from July to August 2025. The program aimed to improve community knowledge, skills, and awareness regarding hydroponic cultivation, apply simple planting techniques, and encourage entrepreneurial development among residents. The vegetables cultivated included mustard greens and kale using a floating hydroponic system with styrofoam media. The implementation methods consisted of technical guidance, socialization, workshops, and direct practice related to cultivation techniques, preparation of plant nutrients, and monitoring plant growth. The results showed that the residents of Bumisari Village already had basic farming experience, while this activity further improved their skills in preparing hydroponic planting media and utilizing land and time productively. In addition, the program increased public knowledge about hydroponic systems and created opportunities for the establishment of new business groups based on hydroponic vegetable cultivation.